The role of atopy in the pathogenesis of bleomycin pulmonary toxicity. (August 2019) - Ozyigit, Leyla Pur; Aktas, Esin Cetin; Senbas, Zarif Asucan; Ozturk, Ayse Bilge; Ozturk, Erman; Ergonul, Mehmet Onder; Tabak, Levent; Ferhanoglu, Burhan; Cetiner, Mustafa; Deniz, Gunnur
Abstract: Introduction: Bleomycin pulmonary toxicity (BPT) is a potentially life-threatening consequence of bleomycin usage in patients. An overproduction of epithelium-derived cytokines, habitually linked to allergic inflammation, has been recently revealed in experimental models of BPT. Methods: We assessed retrospectively our cohort of patients with Hodgkin Lymphoma treated with bleomycin between 2014 and 2016 for their demographic, clinical features, including BPT development, atopy status and risk factors for BPT. Then they were invited for allergy testing and blood sample collection. The samples were stimulated with different stimuli (Bleomycin, IL-33, TSLP) for 24 h on cell culture. The culture supernatants were analysed for TGF-β, Galectin3, Arginin, Amphiregulin, Eotaxin, IFNγ, TNFα, IL1β, 4, 5, 6, 10, 13, 17, MIP-1α, and bleomycin hydrolase (BLH) levels. Results: The cohort consisted of 51 patients showed that atopy was the only significant risk factor for BPT occurrence (OR: 7.2, p = 0.007). Fourteen subjects were included for blood analysis. The analysis of supernatants at the unstimulated condition revealed that BLH and Amphiregulin were significantly lower in patients who had BPT than controls. The BLH cut-off that best identified a history of BPT was 175.31 (Sensitivity: 62.5%, specificity: 100%). Following the stimulation, BLH reduced compared to the unstimulated condition and the difference between groups remained significant (p < 0.05). Conclusion: Our study is the first to report that low levels of bleomycin hydrolase in allergic individuals may be predisposing to a possible pathway of fibrosis.